Niacin-ligated platinum(iv)–ruthenium(ii) chimeric complexes synergistically suppress tumor metastasis and growth with potentially reduced toxicity in vivo. Issue 20 (12th February 2020) - Shu, Liwei; Ren, Lulu; Wang, Yuchen; Fang, Tao; Ye, Zhijian; Han, Weidong; Chen, Chao; Wang, Hangxiang
Abstract : The chimeric Pt(iv )–Ru(ii ) complex was designed to simultaneously release cytotoxic cisplatin and an antimetastatic Ru(ii )–arene compound, thereby producing potent anticancer activity with high drug tolerability in animals. Abstract : Niacin-ligated platinum(iv )–ruthenium(ii ) chimeric complexes (PtRu 1–4 ) have been synthesized and evaluated for their antitumor performance. Using the optimal complex, PtRu-1, we show that this water-soluble chimeric prodrug not only potently inhibits the metastasis and proliferation of tumor cells but also has an unexpectedly higher safety margin in animals compared with the traditionally-used, clinically approved drug cisplatin.